All Hat, No Cattle: Review of Tracey Owens Patton and Sally M. Schedlock, Gender, Whiteness, and Power in Rodeo: Breaking Away from the Ties of Sexism and Racism - Vaught, Jeannette (Humanimalia, 2013)
Tracey Owens Patton and Sally M. Schedlock. Gender, Whiteness, and Power in Rodeo: Breaking Away from the Ties of Sexism and Racism. Lanham: Lexington Books, 2012. Xxxii + 218 pp. 70.00 hb.